2015
DOI: 10.1007/s00595-015-1169-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis in cardiovascular research

Abstract: Advances in mass spectrometry technology and bioinformatics using clinical human samples have expanded quantitative proteomics in cardiovascular research. There are two major proteomic strategies: namely, “gel-based” or “gel-free” proteomics coupled with either “top-down” or “bottom-up” mass spectrometry. Both are introduced into the proteomic analysis using plasma or serum sample targeting ‘biomarker” searches of aortic aneurysm and tissue samples, such as from the aneurysmal wall, calcific aortic valve, or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…High-throughput LC MS/MS technologies have developed significantly over the last 10 years [ 11 13 ]. Isobaric tags for relative and absolute quantitation (iTRAQ) technology has been applied to find potential early biomarkers for Alzheimer’s disease, gastric adenocarcinoma and AMI [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput LC MS/MS technologies have developed significantly over the last 10 years [ 11 13 ]. Isobaric tags for relative and absolute quantitation (iTRAQ) technology has been applied to find potential early biomarkers for Alzheimer’s disease, gastric adenocarcinoma and AMI [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding proteomics focused on cardiovascular tissues, very few studies have been performed up to now investigating the possible protective effect on diseased animals of food bioactive compounds on the protein expression of aortic tissue testing vitamin E and omega‐3 fatty acids and heart tissue testing resveratrol . Other studies analyzing proteome on diseased cardiovascular tissues , such as calcific aortic valve or infarcted myocardium have reflected important changes in protein induced by disease . However, to the best of our knowledge, no study has reported so far the modulation of aorta and heart proteome by bioactive compounds, specifically phenolic compounds, in healthy animals to address future cardiovascular protection.…”
Section: Introductionmentioning
confidence: 99%
“…This is concordant with some available data suggesting free-radical generation in dogs following transthoracic shocks [ 84 ]. Finally, an increase in peroxisome proliferator-activated receptor γ coactivator 1 (PGC-1) and estrogen-related receptor (ERR)-induced regulator in muscle protein 1 (Perm1), may participate in the regulation of muscle-specific transcriptional programs, such as mitochondrial biogenesis and oxidative metabolism, and adaptation of mitochondrial energy transduction pathways and oxidative metabolism [ 99 ].…”
Section: New Insights From Proteomicsmentioning
confidence: 99%